Midshaft clavicular fractures in adolescents: a comprehensive review of diagnosis and management - MacEwen, Heather L; Morell, Michael; Feeley, Scott; Lopreiato, Nicholas; Renninger, Chris; Song, Daniel (Clinics in shoulder and elbow, 2025)
Midshaft clavicular fractures account for approximately 80% of all clavicle fractures in pediatric and adolescent populations and represent up to 15% of all fractures in adolescents. These injuries commonly result from falls, sports-related trauma, or motor vehicle accidents, with adolescent males experiencing fractures at rates up to three times higher than females. This review examines the diagnosis, classification, and management of these fractures, highlighting the nuances between pediatric and adult treatment approaches. Historically, nonoperative management has been favored, leveraging the adolescent clavicle's remodeling capacity. Recent trends reflect increasing operative interventions, driven by adult studies demonstrating faster recovery and improved functional outcomes in displaced fractures. While nonoperative treatment, using slings or figure-of-8 braces, remains effective for most cases, operative fixation, including open reduction and internal fixation or elastic stable intramedullary nailing, is indicated for open fractures, neurovascular injury, or significant displacement. Studies demonstrate high union rates with both methods, but operative treatment offers quicker return to activity, albeit with higher risks of hardware-related complications. The Function after Adolescent Clavicle Trauma and Surgery study notably supports nonoperative management, showing similar long-term functional outcomes compared to operative treatment. Future research should focus on refining patient-reported outcome measures specific to adolescents and identifying subsets of patients who may benefit from surgery. Shared decision-making remains crucial for optimal patient-centered care.